2010
DOI: 10.1182/blood-2009-11-255026
|View full text |Cite
|
Sign up to set email alerts
|

Cross talk between the bone and immune systems: osteoclasts function as antigen-presenting cells and activate CD4+ and CD8+ T cells

Abstract: The bone and immune systems are closely related through cellular and molecular interactions. Because bone-resorbing osteoclasts (OCs) are derived from the monocyte/macrophage lineage, similar to dendritic cells (DCs), we hypothesized that OCs could serve as antigen-presenting cells (APCs) to activate T cells. In this study, OCs were generated from human monocytes with stimulation by receptor activator of nuclear factor kappaB ligand (RANKL) and macrophage colony-stimulating factor (M-CSF). Results showed that,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
168
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(173 citation statements)
references
References 38 publications
(47 reference statements)
3
168
0
2
Order By: Relevance
“…Because OCs can function as APCs, 13 we measured CD80/86 molecules, which are expressed by APCs and involved in T-cell co-stimulation. CD80 expression was significantly induced, whereas CD86 was slightly upregulated in OCs compared with monocytes ( Figure 1C).…”
Section: Inhibitory Immune Molecules Are Upregulated During Osteoclasmentioning
confidence: 99%
“…Because OCs can function as APCs, 13 we measured CD80/86 molecules, which are expressed by APCs and involved in T-cell co-stimulation. CD80 expression was significantly induced, whereas CD86 was slightly upregulated in OCs compared with monocytes ( Figure 1C).…”
Section: Inhibitory Immune Molecules Are Upregulated During Osteoclasmentioning
confidence: 99%
“…Osteoclasts selectively recruit and activate CD8 T cells (17,18). The osteoclast-recruited CD8 T cells express CD25 and FoxP3, and therefore are defined as osteoclast-induced regulatory CD8 T cells (19).…”
Section: Pacificimentioning
confidence: 99%
“…Although several recent studies confirmed immunological properties of bone cells [19][20][21][22]24], direct chemotactic and immunomodulatory effects of OBL and OCL have not been precisely determined. In the co-culture model we demonstrated both the ability of lymphocytes to affect bone cell differentiation and their chemotactic properties, and of bone cells to modulate the cytokine and activation profile of lymphoid cells.…”
Section: Discussionmentioning
confidence: 99%
“…OCL, expressing MHC-I/II and costimulatory molecules, can uptake soluble antigens serving as antigen-presenting cells for alloreactive T lymphocytes [24]. In response to immune cells these bone cells produce cytokines, chemokines, extracellular matrix proteins and other inflammatory mediators [25][26][27].…”
Section: Introductionmentioning
confidence: 99%